Unemployment versus Happiness in Portugal - Caleiro, António (2012)
In traditional terms, the wealth of an economy is measured by its level of production. More recently it has been suggested another measure based on the degree of happiness, which is associated to the levels of satisfaction or quality of life. By some considered paradoxical is the fact that those two measures do not appear to be perfectly correlated. In fact, there are poorer countries in terms of production, which are characterized by higher degrees of happiness. Furthermore, reality evidences that, even in times of economic crisis, the degree of happiness may increase. These are the facts that we seek to clarify, from the viewpoint of the Economics of Happiness, through the analysis of the relationship between happiness and unemployment in Portugal.